Computational trust evaluation algorithm for cloud models using fuzzy logic approach. (19th November 2021) - Thakare, Vaishali Ravindra; K., John Singh
Cloud computing offers several advantages over traditional computing models in industries, so applications which are developed for smart cities requires large amount of storage. Hence, smart cities applications are using cloud computing technologies to manage their applications with great flexibility and availability. To achieve a satisfactory level of trust, we propose a computational trust evaluation algorithm using fuzzy logic approach. In this paper, C-FTEM is designed to strengthen the security at data storage for smart cities and evaluated to prove its effectiveness.